SISTEM PENDUKUNG KEPUTUSAN PEMBERIAN KREDIT MENGGUNAKAN METODE ELECTRE (Studi Kasus : Koperasi Kredit Immaculata) - Mayela Wete; Yoseph P.K Kelen; Siprianus S. Manek (Jurnal Teknologi Informasi: Jurnal Keilmuan dan Aplikasi Bidang Teknik Informatika, 2023)
The Immaculata Credit Cooperative is a cooperative organization whose mission is to advance the Immaculata Credit Cooperative as a reliable, independent and professional microfinance empowerment institution. One of the cooperative sectors is the credit sector because credit is a source of financing for cooperatives. Lending at the Immaculata Credit Cooperative is currently still subject to manual analysis by the credit committee, so that an inaccurate determination of credit granting can increase the number of bad or default loans. Therefore the researcher proposes to build a decision support system using the electre method where the output of the electre method calculation is in the form of ranking so that it can determine recommended prospective customers by looking at 5 assessment criteria including income, length of time to return, occupation, age, and collateral. The results of this study are in the form of desktop-based applications that can make it easier for cooperatives, especially credit committees, to determine which customers to recommend.